New colloidal chromic radiophosphate (P32)for local irradiation of the central nervous system - Anghileri, Leopoldo José; Marqués, Roberto Oscar (Elsevier BV, 1967)
Fil: Anghileri, Lepoldo José Comisión Nacional de Energía Atómica; Argentina